Pengaruh Aplikasi CapCut: Menyelami Kreativitas dengan Ragam Template Video yang Memukau pada Generasi Z - Sekaringtyas, Fia Wahyu; Djuniadi, Djuniadi; Hastawan, Ahmad Fashiha (Universitas Mercu Buana, 2024)
Technology, especially video editing apps like CapCut, has become an integral part of Generation Z's life in the digital age. CapCut provides intuitive features and a variety of templates to create engaging video content without the need for complex editing skills. In interviews with Generation Z students, CapCut's key features such as crop, speed, audio, text, transitions, filters, overlays, and templates were found to be attractive and supportive in the creative process. Nonetheless, there is a need to continue developing the app by adding more template options and providing greater flexibility for users in customizing content. Thus, CapCut can continue to be a relevant and effective tool for Generation Z in expressing themselves in the ever-evolving digital era.